2017
DOI: 10.1016/j.supflu.2017.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and cytotoxic activity of essential oils and extracts of Satureja montana L., Coriandrum sativum L. and Ocimum basilicum L. obtained by supercritical fluid extraction

Abstract: Antioxidative and cytotoxic activity of essential oils and extracts of Satureja montana L., Coriandrum sativum L. and Ocimum basilicum L. obtained by supercritical fluid extraction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 46 publications
6
31
0
Order By: Relevance
“…The superior AO capacity of both essentials oils and extracts of Lamiaceae species in comparison to Apiaceae observed was found to be in good agreement with literature data . Based on the results presented in Table , it can be concluded that 70% ethanol is more efficient solvent in both types of extraction.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The superior AO capacity of both essentials oils and extracts of Lamiaceae species in comparison to Apiaceae observed was found to be in good agreement with literature data . Based on the results presented in Table , it can be concluded that 70% ethanol is more efficient solvent in both types of extraction.…”
Section: Resultssupporting
confidence: 86%
“…The Lamiaceae species were reported to possess a wide range of biological activity and wide diversity of phytochemicals . Ocimum basilicum L. (basil) and Satureja montana L. (winter savory) are well known aromatic plants from Lamiaceae family with proven AO capacity . These aromatic plants are commonly used as flavouring agents in cosmetic industry and as culinary herbs in traditional cuisine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synergistic and also additive interactions between coriander essential oil/linalool and selected antibiotics might be attributed, to a great extent, to the membrane permeabilization activity of the former which facilitates the penetration of antibiotics and consequently their action inside bacterial cell (inhibition of cell wall biosynthesis for b-lactam antibiotics, inhibition of protein synthesis for erythromycin, clindamycin, tetracycline and gentamicin, inhibition of DNA replication for ciprofloxacin) (Kohanski et al 2010). Furthermore, it is worth mentioning that the MICs of coriander essential oil and linalool reported in the present study (5Á44 and 5Á36 lg ml À1 respectively) are significantly lower than the concentrations found to be cytotoxic against human cells: IC 50 = 751 and 1253 lg ml À1 for coriander essential oil and linalool against MRC-5 and GM07492A normal human lung fibroblasts respectively (Souza et al 2016;Elgndi et al 2017), IC 50 = 81Á5, 72Á7 and 64Á7 lg ml À1 at 24, 48 and 72 h, respectively, for linalool against human hepatoma G2 cells (Erdogan and Ozkan 2017). According to Park et al 2012, the concentrations of linalool should be kept below 0Á4 mg ml À1 when used in oral hygiene products.…”
Section: Evaluation Of Antibacterial Interactionsmentioning
confidence: 51%
“…; Elgndi et al . ), IC 50 = 81·5, 72·7 and 64·7 μ g ml −1 at 24, 48 and 72 h, respectively, for linalool against human hepatoma G2 cells (Erdogan and Ozkan ). According to Park et al .…”
Section: Resultsmentioning
confidence: 98%